PENGARUH SERVICE QUALITY, WEBSITE QUALITY, BRAND REPUTATION, TRUST, DAN PERCEIVED RISK TERHADAP PURCHASE INTENTION - Bernika, Cindy; Ekawanto, Iwan (Transpublika Publisher, 2023)
The aim of this study was to determine the effect of service quality, website quality, brand reputation, trust, and perceived risk on consumer purchase intentions. The sampling technique used was purposive sampling with 216 respondents. Data collection used an online questionnaire with a Liker scale of 1 to 5. This study used the Structural Equation Modeling (SEM) method through the AMOS program to process the data. The results showed that service quality did not have a positive effect on consumer purchase intentions in Jakarta, website quality did not have a positive effect on consumer purchase intentions in Jakarta, brand reputation had a positive effect on consumer purchase intentions in Jakarta, trust had a positive effect on consumer purchase intentions in Jakarta, and perceived risk did not have a positive effect on consumer purchase intentions in Jakarta.